2008
DOI: 10.3998/ark.5550190.0009.e14
|View full text |Cite
|
Sign up to set email alerts
|

Regio-orientation in condensation of aminopyrazoles with 1,3-difunctional reagents: synthesis of new pyrazolo[1,5-a]pyrimidines; pyrazolo[3,4-d]pyridazines and 2,4-dihydropyrano[2,3-c]pyrazoles

Abstract: Pyrazolo [1,5-a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The structures of synthesized compounds were confirmed by a variety of spectroscopic techniques, including 1 H and 13 C NMR, mass spectroscopy, IR, and elemental analysis. Elnagdi et al 6,1820 reported that the reaction of enaminoni-trile 1 with aromatic diazonium salts affords arylhydrazones 2 , which are readily converted into arylazoaminopyrazoles 3 . Our work wanted to determine if 4-arylazo-2H-pyr- azol-3-ylamine derivatives could be used as precursors to arylazo-pyrazolo[1,5-a]pyrimidin-7-ylamines (and pyrimi-din-7-ones).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of synthesized compounds were confirmed by a variety of spectroscopic techniques, including 1 H and 13 C NMR, mass spectroscopy, IR, and elemental analysis. Elnagdi et al 6,1820 reported that the reaction of enaminoni-trile 1 with aromatic diazonium salts affords arylhydrazones 2 , which are readily converted into arylazoaminopyrazoles 3 . Our work wanted to determine if 4-arylazo-2H-pyr- azol-3-ylamine derivatives could be used as precursors to arylazo-pyrazolo[1,5-a]pyrimidin-7-ylamines (and pyrimi-din-7-ones).…”
Section: Resultsmentioning
confidence: 99%
“…1517 Arylazopyrazolo[1,5-a]pyrimidines were prepared by condensing aminoarylazopyrazoles with β-bifunctional reagents using methodologies initially established in our laboratories. 1820…”
Section: Introductionmentioning
confidence: 99%
“…Enaminonitriles are important intermediates for the preparation of heterocyclic compounds possessing diverse biological activities. They are of particular interest as very promising reagents for cascade heterocyclization, which will undoubtedly become one of the main approaches to the targeted synthesis of heterocycles in the near future, in the rapidly-rising field of combinatorial chemistry [1]- [3]. Non-steroidal anti-inflammatory drugs (NSAIDs) represent a heterogeneous family of pharmacologically active compounds used to alleviate acute and chronic inflammation, pain and fever.…”
Section: Introductionmentioning
confidence: 99%